Dana Non-Halal pada Bank Umum Syariah: Telaah Berbagai Sudut Pandang - Dewi, Liana; Rohman, Pupun Saepul; Firmansyah, Atep; Khaer, Rijalul; Dewi, Fertika Puspita (POLITEKNIK LP3I, 2024)
The dualism of the banking system in Indonesia led to the formation of conventional banks and sharia banks. Historically, banks with conventional systems have been around longer than sharia banks. This opens up the possibility of transactions between conventional banks and Islamic banks. Interest income is often obtained by Islamic banks from transactions with conventional banks. Islamic banks recognize interest income from conventional banks into non-halal funds so that special treatment is required in their allocation in accordance with Islamic law. There are several differences of opinion regarding the allocation of non-halal funds by Islamic banks in various related research results. This research aims to gain an understanding regarding the allocation of non-halal funds based on various points of view from research results. The method used in this research is Literature Review. The source article used is a scientific article that discusses the handling of non-halal funds and was published from 2010 to 2024. The research results show that the allocation of non-halal funds practiced by banks and sharia financial institutions is currently in accordance with Islamic law, but a small portion still gives the opposite result.